Association between systemic immune-inflammation index, systemic inflammation response index, and adverse outcomes in aneurysmal subarachnoid hemorrhage: a meta-analysis - Hao, Yihong; Zhao, Jianfang; Han, Jie; Hao, Dajiang (Frontiers in Neurology, 2025)
PurposeThis systematic review seeks to explore the link of the systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI), to adverse outcomes (AOs) in aneurysmal subarachnoid hemorrhage (aSAH). The findings may provide scientific evidence to enable the timely identification of patients at high risk and guide the formulation of personalized treatment strategies.Patients and methodsPubMed, Cochrane, Embase, and Web of Science databases were comprehensively retrieved from inception to August 10, 2024. The Newcastle-Ottawa Scale (NOS) was leveraged for appraise the quality of the encompassed studies. Statistical analyses were undertaken via Stata 17.0, and a bivariate mixed-effects model was applied for diagnostic value evaluation.ResultsSixteen studies involving 4,510 aSAH individuals were encompassed. The meta-analysis demonstrated SII as a predictor of poor 90-day outcomes [Odds Ratio (OR) = 1.94, 95% Confidence Interval (CI): 1.35–2.78, p < 0.001], with an area under the receiver operating characteristic (ROC) curve (AUC) of 0.77 (95% CI: 0.73–0.81), sensitivity of 0.71 (95% CI: 0.61–0.79), and specificity of 0.72 (95% CI: 0.62–0.80). Additionally, SII can be utilized for forecasting delayed cerebral ischemia (DCI) (OR = 1.39, 95% CI: 1.35–1.43, p < 0.001), with an AUC of 0.80 (95% CI: 0.76–0.83), sensitivity of 0.75 (95% CI: 0.56–0.88), and specificity of 0.73 (95% CI: 0.62–0.82). SIRI was also found to predict unfavorable 90-day outcomes (OR = 1.19, 95% CI: 1.09–1.30, p < 0.001), with an AUC of 0.79 (95% CI: 0.75–0.82), sensitivity of 0.66 (95% CI: 0.58–0.73), and specificity of 0.76 (95% CI, 0.73–0.80). However, SIRI was not a significant predictor of DCI (OR = 1.37, 95% CI: 0.94–2.02, p = 0.105) or postoperative pneumonia (POP) (OR = 3.73, 95% CI: 0.68–20.35, p = 0.128).ConclusionBoth SII and SIRI serve as predictive biomarkers for unfavorable 90-day outcomes in the aSAH population, with SII also demonstrating predictive value for DCI. While both indices exhibit moderate accuracy, further research is necessitated to validate their clinical utility.Clinical trial registrationhttps://www.crd.york.ac.uk/PROSPERO/, Registration No: CRD42024585116.